2004
DOI: 10.1111/j.1365-2370.2004.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

The MICA‐A4 triplet repeats polymorphism in the transmembrane region confers additional risk for development of psoriatic arthritis in the Croatian population

Abstract: The aim of this study was to investigate possible differences in the frequencies of alleles at the HLA loci and at microsatellite loci within the HLA region among patients suffering from psoriatic arthritis (PsA) and healthy controls. Fifty-eight Croatian PsA patients (28 male and 30 female) and 157 healthy unrelated controls were typed for HLA alleles (A, B, Cw and DRB1) by the polymerase chain reaction-sequence-specific primers (PCR-SSP) method, while microsatellite alleles (D6S265, D6S273, MHC class I chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This allele is associated above all with polyarticular forms (relative risk 9.3 vs. 3.2 for all psoriatic arthritis cases) 38 . In another study, a correlation with MIC‐A‐A9 was not found, but instead, in this Croatian population, a correlation with MIC‐A‐A4 ; 39 A polymorphism of the TNF genes ( TNFα‐308 and TNFβ‐252 (A)) has been observed in peripheral psoriatic arthritis 24,40–42 . This is interesting because the polymorphism of TNFα‐30 8 is associated with elevated levels of TNF‐α 40,43 .…”
Section: What Can We Learn From Genetic Studies?mentioning
confidence: 69%
“…This allele is associated above all with polyarticular forms (relative risk 9.3 vs. 3.2 for all psoriatic arthritis cases) 38 . In another study, a correlation with MIC‐A‐A9 was not found, but instead, in this Croatian population, a correlation with MIC‐A‐A4 ; 39 A polymorphism of the TNF genes ( TNFα‐308 and TNFβ‐252 (A)) has been observed in peripheral psoriatic arthritis 24,40–42 . This is interesting because the polymorphism of TNFα‐30 8 is associated with elevated levels of TNF‐α 40,43 .…”
Section: What Can We Learn From Genetic Studies?mentioning
confidence: 69%
“…In a Spanish study of 120 PsA patients, 50 psoriasis patients and 175 healthy control subjects, Cw6 was associated with psoriasis but not PsA. In a Croatian population of 58 PsA patients and 157 healthy control subjects, development of PsA was associated with the MICA-A4 (p c = 0.017), but not the previously identified MICA-A9 triplet [17]. In a Croatian population of 58 PsA patients and 157 healthy control subjects, development of PsA was associated with the MICA-A4 (p c = 0.017), but not the previously identified MICA-A9 triplet [17].…”
Section: Genetic Factorsmentioning
confidence: 79%
“…However, polymorphisms on STR-MICA may be immunologically relevant, because they have been associated with autoimmune dysfunctions like BehÈet's disease and psoriatic arthritis [15,34]. In the context of its immunological function, the MICA gene itself was described as a ligand for the NKG2D/DAP10 stimulatory receptor complex [35], expressed on natural killer cells, gd T cells and CD8 ϩ ab T cells, triggering cytolysis mediated by NKG2D-bearing cells [36] and also costimulating CD8 ϩ ab T lymphocytes [37].…”
Section: Discussionmentioning
confidence: 99%